Preparation method and application of double-ligand MOF photocatalyst

By introducing porphyrins and polycyclic aromatic hydrocarbons as biligands in MOF, an efficient electron transfer channel is constructed, which solves the problem of low NADH regeneration efficiency in existing photocatalytic methods, and achieves the effect of efficient NADH regeneration under visible light.

CN119823403APending Publication Date: 2025-04-15CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510008487.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing photocatalytic methods have limited light-grabbing capabilities and high electron-hole recombination probability in NADH regeneration, resulting in inefficiency.

Method used

By introducing photosensitive chromophore porphyrins and electron-rich polycyclic aromatic hydrocarbons as biligands into metal organic frame materials (MOFs), an efficient electron transfer channel is constructed, broadening the material's light absorption range and promoting charge separation.

Benefits of technology

The cyclic regeneration of high-efficiency NADH in visible light is achieved, and the photocatalyst absorption range and charge transfer efficiency are improved without the need for precious metal cocatalysts and electronic media.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823403A_ABST
    Figure CN119823403A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a double-ligand MOF photocatalyst, and belongs to the technical field of organic metal hybrid nano materials, and the prepared double-ligand MOF photocatalyst has excellent visible light response and photochemical conversion properties, and can realize efficient conversion of NADH under visible light. According to the technical scheme, the method comprises the following steps: (1) adding tetravalent zircon salt, a porphyrin compound and a polycyclic aromatic hydrocarbon compound into an organic solvent; after dissolving, introducing organic acid and carrying out ultrasonic treatment to dissolve the organic acid; and transferring the obtained solution to a reaction kettle, heating to react for a certain time, cooling, washing with an organic solvent, and drying to obtain the MOF photocatalyst with double ligands. The obtained composite photocatalyst can be applied to efficient regeneration of NADH (Nicotinamide Adenine Dinucleotide).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of organic nanomaterials, and in particular relates to a method for preparing a MOF material based on a dual-ligand structure with light absorption, photoelectric conversion and photochemical conversion functions, and its application in efficient photocatalytic NADH regeneration. Background Art

[0002] In recent years, due to the continuous growth of the world's population, the problem of energy shortage has become increasingly apparent. The excessive use of fossil fuels by humans in production and life has also caused a series of serious environmental problems such as greenhouse effect and climate anomaly, which has seriously hindered the sustainable development of human society (Ma X. et al., Materials Science in Semiconductor Processing 2022, 105, 104734). Therefore, in order to balance the contradiction between energy supply and environmental problems, reducing the use of non-renewable energy and developing new energy have become a top priority. Due to the easy availability, cleanliness, cheapness and inexhaustible characteristics of solar energy, it has become an important sustainable energy source. Among them, the conversion of light energy to chemical energy has become an important research direction in the field of new energy. Green plants in nature show us methods of solar energy utilization and CO2 conversion. Therefore, the artificial photosynthetic system constructed in imitation of natural photosynthesis is one of the most promising methods to alleviate environmental pollution and cope with energy crises (Wang Z. et al., Chemical Reviews 2019, 48 (7), 2109-2125).

[0003] In the photosynthesis of plants, light energy is converted into chemical energy by photosynthetic phosphorylation in the light reaction stage, and stored in nicotinamide adenine dinucleotide (NADH) and adenosine triphosphate (ATP) energy storage molecules, and energy is transferred to carbon dioxide and reduced to organic matter by enzyme catalysis, wherein the coenzyme NADH is a bridge connecting photocatalysis and enzyme catalysis. Therefore, the continuous supply (regeneration) of NADH in artificial photosynthetic systems is particularly important (Yadav R. et al., Journal of the American Chemical Society 2012, 134 (28), 11455-11461). At present, there are two main problems in promoting NADH regeneration by photocatalysis, namely, limited light-harvesting capacity and high electron-hole recombination probability. Therefore, the present invention, on the basis of simulating the photosynthetic system structure and composition in nature, introduces photosensitivity chromophore porphyrin and electron-rich polycyclic aromatic hydrocarbons (PAHs) as connecting ligands into metal organic framework materials (MOF) at the same time. The porphyrin molecules and polycyclic aromatic hydrocarbons with conjugated macrocyclic structures are used as light-harvesting units at the same time, which broadens the light absorption range of the material. The internal electric field is formed through the energy band difference between porphyrin and polycyclic aromatic hydrocarbons, which promotes charge separation and the transfer of photogenerated electrons. The hybrid nanomaterial can efficiently regenerate NADH under visible light. Summary of the invention

[0004] The present invention proposes a method for preparing a MOF photocatalyst with a dual ligand structure. The MOF photocatalyst prepared according to the method has good visible light responsiveness and photocatalytic activity, and can achieve efficient cyclic regeneration of NADH under visible light.

[0005] In order to achieve the above object, the invention provides a method for preparing a dual-ligand MOF photocatalyst, comprising the following steps:

[0006] S1: adding a tetravalent zirconium salt, a porphyrin compound, a polycyclic aromatic hydrocarbon compound and an organic acid to N,N-dimethylformamide, stirring and dissolving the mixture to obtain a mixed solution;

[0007] S2: The mixed solution is transferred to a reactor for solvothermal reaction. After the reaction is completed, the mixed solution is cooled to room temperature, washed and dried to obtain a dual-ligand MOF material.

[0008] Among them, the tetravalent zirconium salt is selected from at least one of zirconium oxychloride octahydrate, zirconium nitrate and zirconium chloride; the porphyrin compound is selected from at least one of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin, 5,10,15,20-tetrakis(4-pyridyl)porphyrin and dicarboxyphenylporphyrin; the polycyclic aromatic hydrocarbon compound is at least one of 1,2,4,5-tetrakis(4-carboxyphenyl)benzene, 5',5""-(anthracene-9,10-diyl)bis(([1,1':3',1"-terphenyl]-4,4"-dicarboxylic acid)) and 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene.

[0009] Preferably, the molar ratio of the tetravalent zirconium salt, the porphyrin compound and the polycyclic aromatic hydrocarbon compound added in S1 is 1:(0-1):(1-0).

[0010] Preferably, the organic acid is selected from at least one of formic acid, acetic acid and benzoic acid, and its concentration is 1-10 mol L -1 .

[0011] Preferably, the stirring and dissolving time is 30-60 minutes.

[0012] Preferably, the solvent thermal reaction temperature is 110-130° C., and the reaction time is 24-48 hours.

[0013] Preferably, the washing liquid is selected from at least one of N,N-dimethylformamide, acetone, methanol and ethanol.

[0014] Preferably, the material is dried in a vacuum drying oven at 60 degrees Celsius for 24 hours in S2.

[0015] A dual-ligand MOF photocatalyst uses zirconium oxygen cluster nodes to arrange porphyrin ligands and polycyclic aromatic hydrocarbon ligands in an orderly manner inside the MOF, constructing an efficient electron transfer channel, effectively broadening the light absorption range of the MOF material, and giving it excellent photoelectric conversion and photocatalytic capabilities.

[0016] A dual-ligand MOF photocatalyst with excellent photoelectric conversion ability and small interfacial resistance can achieve efficient regeneration of reduced nicotinamide adenine dinucleotide (NADH) under visible light.

[0017] Compared with the prior art, the advantages and positive effects of the present invention are:

[0018] 1. A new dual-ligand MOF photocatalyst was successfully synthesized using a simple solvothermal method. The introduction of dual ligands cleverly expanded the absorption range of visible light and produced a mesoporous structure; effectively improving the adsorption and catalytic capabilities of MOF materials.

[0019] 2. The difference in electron donation / withdrawal ability between the two ligands is beneficial to the separation of photogenerated electron-hole pairs in MOF materials, which makes the excitation and transfer rate of photogenerated electrons faster and the photocatalytic performance better.

[0020] 3. Compared with the prior art, the preparation method provided by the present invention is simple and the conditions are mild. The obtained photocatalyst has a stable structure and excellent light absorption and photoelectric conversion capabilities. At the same time, it can obtain a higher NADH conversion efficiency in the absence of precious metal co-catalysts and electron mediators. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1A A scanning electron microscope photograph of the zirconium-porphyrin MOF photocatalyst provided in an embodiment of the present invention;

[0022] Figure 1B A scanning electron microscope photograph of the zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF photocatalyst provided in an embodiment of the present invention;

[0023] Figure 2 X-ray diffraction spectra of zirconium-porphyrin MOF and zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF photocatalysts provided in the embodiments of the present invention;

[0024] Figure 3 Diffuse reflectance UV-visible spectra of zirconium-porphyrin MOF and zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF photocatalysts provided by the embodiments of the present invention;

[0025] Figure 4A The optical band gap spectrum of the zirconium-porphyrin MOF photocatalyst provided in the embodiment of the present invention;

[0026] Figure 4BThe optical band gap spectrum of the zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF photocatalyst provided in the embodiment of the present invention;

[0027] Figure 5A The Mott-Schottky curve of the zirconium-porphyrin MOF photocatalyst provided in the embodiment of the present invention;

[0028] Figure 5B The Mott-Schottky curve of the zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF photocatalyst provided in the embodiment of the present invention;

[0029] Figure 6 Schematic diagram of the energy band structure of the zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF and the zirconium-porphyrin MOF photocatalyst provided in the embodiments of the present invention;

[0030] Figure 7 The photocurrent response curves of the zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF and the zirconium-porphyrin MOF photocatalyst provided in the embodiments of the present invention;

[0031] Figure 8 Electrochemical impedance spectroscopy of zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF and zirconium-porphyrin MOF photocatalyst provided in the embodiments of the present invention;

[0032] Fig. 9 The relationship curve between NADH generation rate and irradiation time when the porphyrin monomer, zirconium-porphyrin MOF and zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF provided in the embodiments of the present invention are used as photocatalysts. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described examples are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The present invention proposes a method for preparing a dual-ligand MOF photocatalyst, which is characterized by comprising the following steps:

[0035] S1: adding a tetravalent zirconium salt, a porphyrin compound, a polycyclic aromatic hydrocarbon compound and an organic acid to N,N-dimethylformamide, stirring and dissolving the mixture to obtain a mixed solution;

[0036] S2: The mixed solution is transferred to a reactor for solvothermal reaction. After the reaction is completed, the mixed solution is cooled to room temperature, washed and dried to obtain a dual-ligand MOF material.

[0037] In a closed system of a specific solvent, metal ions or metal clusters (nodes) and organic ligands (connectors) react at a certain temperature and the autogenous pressure of the solution, and self-assemble through coordination bonds to form MOF crystals with a periodic structure. Among them, organic ligands play a vital role in MOFs and have an important impact on the properties and functions of MOFs. By designing and selecting highly sensitive chromophores or complementary mixed ligands, the crystal structure, light absorption range and photoelectric conversion ability of MOFs can be directly affected, thereby affecting the adsorption, separation and catalytic properties of MOFs. The advantage of this reaction is that it is based on the solvothermal method, reacts under high temperature and high pressure conditions to generate MOF materials. The reaction is simple to operate and highly controllable, and can be customized to synthesize MOF materials with controllable structures.

[0038] The polycyclic aromatic hydrocarbon compound is at least one of 1,2,4,5-tetrakis(4-carboxyphenyl)benzene, 5',5""-(anthracene-9,10-diyl)bis(([1,1':3',1"-terphenyl]-4,4"-dicarboxylic acid)) and 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene. Among them, the tetravalent zirconium salt is selected from at least one of zirconium oxychloride octahydrate, zirconium nitrate and zirconium chloride; the porphyrin compound is selected from at least one of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin, 5,10,15,20-tetrakis(4-pyridyl)porphyrin and dicarboxyphenylporphyrin; the polycyclic aromatic hydrocarbon compound is at least one of 1,2,4,5-tetrakis(4-carboxyphenyl)benzene, 5',5""-(anthracene-9,10-diyl)bis(([1,1':3',1"-terphenyl]-4,4"-dicarboxylic acid)) and 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene.

[0039] In the present embodiment, the main function of zirconium salt is to provide a precursor of the metal node in MOF, and the height of its concentration will directly affect the speed and efficiency of the reaction, thereby affecting the purity and quality of the final product. Therefore, the concentration of zirconium salt needs to be reasonably set. Porphyrin compounds give MOF materials light response characteristics. In the present invention, by assembling two ligands with different electronic properties into MOF at the same time, an efficient electron transfer channel is constructed, electron-hole recombination is suppressed, and charge separation and transmission efficiency are improved. In addition, the selection of porphyrin and polycyclic aromatic hydrocarbon ligands is very important for the construction of mixed ligand MOF materials. The selection of ligands affects its reactivity, and the activity of different organic ligands combined with zirconium oxygen clusters is different, which affects the internal structure of MOF materials and the perfection of crystals. In this embodiment, 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin, 5,10,15,20-tetrakis(4-pyridyl)porphyrin and dicarboxyphenylporphyrin are used as porphyrin ligands, and 1,2,4,5-tetrakis(4-carboxyphenyl)benzene, 5',5""-(anthracene-9,10-diyl)bis(([1,1':3',1"-terphenyl]-4,4"-dicarboxylic acid)) and 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene are used as polycyclic aromatic hydrocarbon ligands to obtain MOF photocatalysts with a dual ligand structure.

[0040] In a preferred embodiment of the present invention, the molar ratio of the added tetravalent zirconium salt, porphyrin compound and polycyclic aromatic hydrocarbon compound is 1: (0-1): (1-0). Considering the preparation of the MOF photocatalyst with a dual ligand structure by the above-mentioned preparation method, the selected tetravalent zirconium salt, porphyrin compound and polycyclic aromatic hydrocarbon compound, their respective concentration settings and matching ratios will have a crucial impact on the final target product. For example, the type and concentration of the added porphyrin compound and polycyclic aromatic hydrocarbon compound are different, and the morphology of the obtained material will also change. This is also the case in this embodiment where the molar ratio of the above three components is limited to the above-mentioned range.

[0041] In a preferred embodiment of the present invention, the organic acid is selected from at least one of formic acid, acetic acid and benzoic acid, and its concentration is 1-10 mol L -1 The main function of organic acid is to change the pH value of the reaction solution and adjust the reduced and oxidized states of metal ions, thereby affecting the crystalline structure and properties of MOF. In addition, in MOF synthesis, acid can also prevent other coordinated anions (such as F - 、CO3 2- PO4 3- etc.) destroy the framework structure of MOF.

[0042] In a preferred embodiment of the present invention, the heating temperature is 110-130°C, and the heating time is 24-48 hours. In this embodiment, the reaction parameters in the heating reaction and the calcination reaction can be selected by those skilled in the art within the above range according to actual needs. For example, the heating temperature can be 110, 120, 130°C or any point value within the above range, and the time can be 24, 36, 48 hours or any point value within the above range, and a MOF photocatalyst with a dual ligand structure can be obtained.

[0043] In a preferred embodiment of the present invention, the organic solvent is at least one of N, N-dimethylformamide, acetonitrile, and dimethyl sulfoxide; the washing liquid is selected from at least one of N, N-dimethylformamide, acetone, methanol, and ethanol. It should be noted that the organic solvent can dissolve the metal precursor and the organic ligand to form a uniform solution, which helps to form a uniform crystal nucleus and then grow a uniform crystal. In addition, the type and proportion of the organic solvent can affect the growth rate and morphology of the MOF crystal. By adjusting the solvent ratio and reaction conditions, the size and morphology of the MOF can be regulated. The washing liquid is selected from at least one of N, N-dimethylformamide, acetone, methanol, and ethanol. It can be understood that washing with organic solvents such as N, N-dimethylformamide is to remove unreacted organic ligands and metal salts on the surface of the MOF material, and the main purpose is to improve the purity and quality of the product. Although the organic solvent can remove excess ligands and metal salts, if added too much, it may affect the purity and quality of the product. Therefore, by removing the organic solvent in an appropriate manner, a purer and better quality photocatalyst can be obtained. For example, N,N-dimethylformamide can be removed by washing with ethanol, and those skilled in the art can select it according to the actual situation to achieve their purpose.

[0044] The embodiment of the present invention provides a MOF photocatalyst with a dual ligand structure prepared by the preparation method described in any of the above embodiments. The present invention adopts a dual ligand strategy to successfully prepare a new zirconium-based MOF containing porphyrin and polycyclic aromatic hydrocarbons. The obtained sample has good light absorption and charge transfer properties. The introduction of dual ligands cleverly expands the absorption range of visible light and improves the efficiency of charge separation, which plays an important role in improving its photoelectric conversion and catalytic activity.

[0045] The embodiment of the present invention provides an application of the MOF photocatalyst with a dual ligand structure according to the above embodiment in a catalytic NADH regeneration method. In a preferred embodiment, the NADH conversion rate can reach more than 55% within 60 minutes. In this embodiment, the prepared MOF photocatalyst with a dual ligand structure exhibits excellent photocatalytic effect, not only having excellent photoelectric conversion ability and low interface resistance, but also realizing oxidized nicotinamide adenine dinucleotide (NAD+ ) to reduced nicotinamide adenine dinucleotide (NADH), while storing light energy in NADH in the form of chemical energy.

[0046] In order to more clearly and in detail introduce the preparation method and application of the MOF photocatalyst with a dual ligand structure provided by the embodiments of the present invention, it will be described below in conjunction with specific embodiments.

[0047] Example 1

[0048] S1: adding zirconium tetrachloride, 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin, 1,2,4,5-tetrakis(4-carboxyphenyl)benzene and formic acid to N,N-dimethylformamide, stirring for 30 minutes to dissolve, and obtaining a mixed solution;

[0049] S2: The mixed solution was transferred to a reactor and reacted at 110 degrees Celsius for 24 hours. After the reaction was completed, it was cooled to room temperature, washed with N,N-dimethylformamide, and dried in a vacuum drying oven at 60 degrees Celsius for 24 hours to obtain a composite MOF material 1.

[0050] Example 2

[0051] S1: adding zirconium oxychloride octahydrate, dicarboxyphenylporphyrin, 1,2,4,5-tetrakis(4-carboxyphenyl)benzene and formic acid to N,N-dimethylformamide, stirring for 30 minutes to dissolve, and obtaining a mixed solution;

[0052] S2: The mixed solution was transferred to a reactor and reacted at 130 degrees Celsius for 24 hours. After the reaction was completed, it was cooled to room temperature, washed with N,N-dimethylformamide, and dried in a vacuum drying oven at 60 degrees Celsius for 24 hours to obtain a composite MOF material 2.

[0053] Example 3

[0054] S1: adding zirconium tetrachloride, 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin, 1,2,4,5-tetrakis(4-carboxyphenyl)benzene and acetic acid to N,N-dimethylformamide, stirring for 60 minutes to dissolve, and obtaining a mixed solution;

[0055] S2: The mixed solution was transferred to a reactor and reacted at 120 degrees Celsius for 24 hours. After the reaction was completed, it was cooled to room temperature, washed with acetone, and dried in a vacuum drying oven at 60 degrees Celsius for 24 hours to obtain a composite MOF material 3.

[0056] Example 4

[0057] S1: adding zirconium tetrachloride, 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin, 5',5""-(anthracene-9,10-diyl)bis(([1,1':3',1"-terphenyl]-4,4"-dicarboxylic acid)) and benzoic acid to N,N-dimethylformamide, stirring for 60 minutes to dissolve, and obtaining a mixed solution;

[0058] S2: The mixed solution was transferred to a reactor and reacted at 110 degrees Celsius for 24 hours. After the reaction was completed, it was cooled to room temperature, washed with acetone, and dried in a vacuum drying oven at 60 degrees Celsius for 24 hours to obtain a composite MOF material 4.

[0059] Example 5

[0060] S1: adding zirconium nitrate, 5,10,15,20-tetrakis(4-pyridyl)porphyrin, 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene and acetic acid to N,N-dimethylformamide, stirring for 60 minutes to dissolve, and obtaining a mixed solution;

[0061] S2: The mixed solution was transferred to a reactor and reacted at 130 degrees Celsius for 24 hours. After the reaction was completed, it was cooled to room temperature, washed with ethanol, and dried in a vacuum drying oven at 60 degrees Celsius for 24 hours to obtain a composite MOF material 5.

[0062] Example 6

[0063] S1: adding zirconium nitrate, 5,10,15,20-tetrakis(4-pyridyl)porphyrin, 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene and benzoic acid to N,N-dimethylformamide, stirring for 30 minutes to dissolve, and obtaining a mixed solution;

[0064] S2: The mixed solution was transferred to a reactor and reacted at 120 degrees Celsius for 24 hours. After the reaction was completed, it was cooled to room temperature, washed with methanol, and dried in a vacuum drying oven at 60 degrees Celsius for 24 hours to obtain a composite MOF material 6.

[0065] Example 7

[0066] Morphological characterization of MOF photocatalysts with dual ligands

[0067] The instrument is a JSM-7900F field emission scanning electron microscope, and the manufacturer of the instrument is JEOL.

[0068] Taking the material obtained in the above embodiment as an example, a small amount of sample is placed in a centrifuge tube, a certain amount of anhydrous ethanol (or water) is added, and ultrasonic treatment is performed at room temperature for 5-10 minutes, and then a small amount of liquid is dropped on a silicon wafer to dry. The silicon wafer is then placed under a scanning electron microscope for characterization, and a scanning electron microscope image of the sample can be obtained.

[0069] Figure 1 is a scanning electron microscope image of zirconium-porphyrin MOF and zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF. The results show that the synthesized dual-ligand zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF is a short rod-like structure. Compared with zirconium-porphyrin MOF, its size is reduced, so it has a larger specific surface area, which makes it have a stronger adsorption capacity for NADH in the water environment to increase the reaction rate.

[0070] Example 8

[0071] Crystal structure characterization of MOF photocatalyst with dual ligands

[0072] The instrument is X Pert PRO MPD diffractometer, and the manufacturer of the instrument is PANalytical of the Netherlands.

[0073] Taking the materials obtained in the above embodiment as an example, the prepared sample is ground into fine powder, and then an appropriate amount of the sample is placed in the sample slot, and then the surface of the sample is flattened with a glass sheet, and then the excess sample outside the sample slot is cleaned to avoid contaminating the test instrument. Then the prepared sample is placed on the instrument table for testing.

[0074] The characteristic X-ray is Cu Kα (λ = 0.154 nm), and the scanning rate (2θ) is 5° min -1 The angle range of the test is 5°-76°. The diffraction pattern of the measured sample is analyzed and processed by Jade software, and then plotted by Origin, and the crystal structure analysis of the sample can be obtained intuitively.

[0075] like Figure 2 As shown, there are X-ray diffraction patterns of MOF materials with a single ligand and MOF materials with mixed ligands, indicating that the prepared MOF materials have good crystallinity, and the experimental curve corresponds well to the simulated curve, indicating that MOF materials with good crystallinity are prepared under these conditions.

[0076] Example 9

[0077] Characterization of photoresponsiveness of MOF photocatalysts with dual ligands

[0078] The test was performed using a diffuse reflectance UV-visible spectrophotometer, model: UV-1700PharmaSpec, at an experimental temperature of 25°C.

[0079] The material obtained in the above embodiment is used as an example to illustrate that the absorption of the synthesized MOF material in the visible light region is measured in combination with a diffuse reflectance UV-visible spectrophotometer. Specifically, ultrafine barium sulfate is used as a reference, and the sample is coated on a barium sulfate sheet and pressed for measurement, with a measurement range of 200-800nm.

[0080] The test results are shown in Figure 4. The MOF material with dual ligands exhibits a wider absorption range than the MOF material with single ligands, indicating that the mixed ligand strategy can significantly improve the utilization of solar energy. The absorption peak of the MOF material with dual ligands at around 400nm can be attributed to polycyclic aromatic hydrocarbons, and the characteristic peaks derived from the porphyrin Q band also appear in the composite material, proving that both porphyrin and polycyclic aromatic hydrocarbon ligands exist in the material.

[0081] Example 10

[0082] Characterization of the energy band structure of MOF photocatalysts with dual ligands

[0083] The following tests were performed using an electrochemical analyzer, model: CHI 660E, at an experimental temperature of 25° C., and the materials obtained in the above embodiment were used as an example for illustration.

[0084] The sample was fixed on ITO conductive glass to make an electrode. Usually, 1 mg of the sample was dispersed in 200 uL of aqueous solution and ultrasonicated for 10 minutes. Then, the solution was dropped on a 1×1 cm 2 on ITO glass and dried at 50°C overnight. Then, 0.1% Nafi on was dropped on the conductive glass deposited with the sample and allowed to dry naturally. All photoelectrochemical measurements were performed in a three-electrode system, with a saturated calomel electrode as the reference electrode, a platinum sheet as the counter electrode, and the sample as the working electrode. A xenon lamp (filter > 400nm) was used as the light source, a CH I660E electrochemical analyzer was used for detection, and the sample was subjected to a Mott-Schottky test using a three-electrode system. The electrolyte solution was a 1 mol / L sodium sulfate solution. The parameter settings of the Mott-Schottky curve diagram centered on the open circuit voltage for the Mott-Schottky test set the starting potential and the ending potential in the range of 0.5-1V, the amplitude to 0.01V, and the frequency to 1000.

[0085] The test results are shown in Figure 5. The flat band potential of zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF is more negative than that of zirconium-porphyrin MOF. The electronegativity of its electrons increases, and the electron reduction ability becomes stronger, so it has better photocatalytic reduction ability. This means that there is a greater potential difference between the two ligands, which can speed up the electron transfer between the ligands.

[0086] Embodiment 11

[0087] Characterization of photocurrent responsiveness of dual-ligand MOF photocatalysts

[0088] The photoelectric response of zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF and zirconium-porphyrin MOF photocatalysts was measured using a three-electrode system using a potentiostat / galvanostatic electrochemical analyzer, model: CHI 660E. The light source was provided by a 300W xenon lamp (CELL-TUV300) equipped with a UV filter (<420nmoff). The ITO electrode was used as the working electrode, the platinum sheet was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode. The sodium sulfate solution containing ascorbic acid was used as the electrolyte. The operation must first be carried out under light-proof conditions.

[0089] The open circuit potential of the sample is measured under the Amperometry Curve mode, and then the photoelectric response curve is measured. When measuring, the measured open circuit potential voltage is first added to the working electrode, and the measurement is kept stable for more than 180 seconds in the dark to prevent the sample potential from affecting the experiment. Then the light is turned on and off, with a time interval of 30 seconds, and this cycle is repeated multiple times to measure the photoelectric response curve.

[0090] A three-electrode electrochemical workstation was used to characterize the photoelectric response behavior of the zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF photocatalyst. As a control, the photocurrent curve of the zirconium-porphyrin MOF is also given. Figure 6 As shown, under light, a stable photocurrent is generated, and when protected from light, the photocurrent disappears, indicating that under light, the zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF photocatalyst generates a large number of photogenerated electrons and transfers them to the electrode, reflecting that the zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF photocatalyst has good photoelectric conversion properties.

[0091] Example 12

[0092] Characterization of Charge Transfer Properties of Dual-ligand MOF Photocatalysts

[0093] The photoelectric effect of zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF photocatalyst was measured using a three-electrode system using a potentiostat / galvanostatic electrochemical analyzer, model: CHI 660E. The light source was provided by a 300W xenon lamp (CELL-TUV300) equipped with a UV filter (<420nm off). The ITO electrode was used as the working electrode, the platinum sheet was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode. The potassium chloride solution containing potassium ferrocyanide was used as the electrolyte.

[0094] The electrochemical impedance of the zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF photocatalyst was characterized by a three-electrode electrochemical workstation. As a control, the Nyquist spectrum of the zirconium-porphyrin MOF is also given. Figure 7As shown, under dark conditions, the arc radius in the high-frequency region of the Nyquist spectrum of the porphyrin / metal sulfide composite photocatalyst 1 is smaller, indicating that the interfacial charge transfer resistance of the photocatalyst is smaller at this time, which is more conducive to the transmission and transfer of electrons.

[0095] Embodiment 13

[0096] Characterization of the photocatalytic performance of MOF photocatalysts with dual ligands

[0097] The test was conducted using an ultraviolet-visible spectrophotometer (model: UV-2450, Shimadzu) at an experimental temperature of 25°C.

[0098] The photocatalytic ability of the zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF and the zirconium-porphyrin MOF photocatalyst provided in the embodiment of the present invention for NADH regeneration is compared, and the specific experimental method is as follows:

[0099] In this example, NADH is used as a model substance for the photocatalytic regeneration experiment. The photocatalyst and the model substance solution are added to a quartz cuvette and mixed evenly. The xenon light source is turned on for preheating. During the test, samples are taken at regular intervals, centrifuged, and detected using a UV-visible spectrometer. The concentration of NADH in the reaction system is determined by measuring the absorbance of the solution at 340 nm.

[0100] like Figure 8 As shown in the figure, compared with zirconium-porphyrin MOF, the zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF sample has a significantly improved NADH regeneration effect, and the regeneration rate can reach about 55%. This shows that the catalytic reduction ability of the zirconium-porphyrin-polycyclic aromatic hydrocarbon MOF sample is very excellent. Figure 8 It can be seen from the NADH conversion rate curve that compared with the zirconium-porphyrin MOF, the zirconium-porphyrin-polycyclic aromatic hydrocarbons MOF sample has a higher conversion rate in promoting NADH regeneration, which greatly shortens the time required for the reaction, indicating that the zirconium-porphyrin-polycyclic aromatic hydrocarbons MOF photocatalyst provided by the present invention has excellent photocatalytic ability and can achieve efficient regeneration of NADH under visible light in the absence of electron mediators and precious metals.

Claims

1. A method for preparing a dual-ligand MOF photocatalyst, characterized in that: The following steps are involved: S1: adding a tetravalent zirconium salt, a porphyrin compound, a polycyclic aromatic hydrocarbon compound and an organic acid to N,N-dimethylformamide, stirring and dissolving the mixture to obtain a mixed solution; S2: The mixed solution is transferred to a reactor for solvothermal reaction. After the reaction is completed, the mixed solution is cooled to room temperature, washed and dried to obtain a dual-ligand MOF material. Among them, the tetravalent zirconium salt is selected from at least one of zirconium oxychloride octahydrate, zirconium nitrate and zirconium chloride; the porphyrin compound is selected from at least one of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin, 5,10,15,20-tetrakis(4-pyridyl)porphyrin and dicarboxyphenylporphyrin; the polycyclic aromatic hydrocarbon compound is at least one of 1,2,4,5-tetrakis(4-carboxyphenyl)benzene, 5',5""-(anthracene-9,10-diyl)bis(([1,1':3',1"-terphenyl]-4,4"-dicarboxylic acid)) and 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the added tetravalent zirconium salt, porphyrin compound and polycyclic aromatic hydrocarbon compound is 1:(0-1):(1-0).

3. The preparation method according to claim 1, characterized in that: The organic acid is selected from at least one of formic acid, acetic acid and benzoic acid, and its concentration is 1-10 mol L -1 .

4. The preparation method according to claim 1, characterized in that: Stir and dissolve for 30-60 minutes.

5. The preparation method according to claim 1, characterized in that: The heating temperature is 110-130°C and the heating time is 24-48 hours.

6. The preparation method according to claim 1, characterized in that: The washing liquid is selected from at least one of N,N-dimethylformamide, acetone, methanol and ethanol.

7. The preparation method according to claim 1, characterized in that: Dry in a vacuum oven at 60 °C for 24 h.

8. A dual-ligand MOF photocatalyst prepared according to the preparation method according to any one of claims 1 to 7.

9. The dual-ligand MOF photocatalyst according to claim 8 has excellent photoelectric conversion ability and small interface transfer resistance, and can achieve efficient regeneration of reduced nicotinamide adenine dinucleotide (NADH) under visible light.

Citation Information

Cited By

  • Novel MOF composite material and preparation method and application thereof

    CN121495133A

  • A novel MOF composite material and a preparation method and application thereof

    CN121495133B